The Effects of the Authentic Task on Preservice Teachers' Achievement - (:unkn) unknown (HACETTEPE UNIV, 2013)
This study aims to investigate the effects of the curriculum based on authentic task on preservice early childhood teachers' academic achievement. It was designed as an experimental study. Data were collected the 50-item and five-point Multiple Choice Achievement Test designed by the researcher for the course Special Instruction Methods I used in the study, a Classical Exam based on criteria in accordance with course content, the 20-item Performance Assessment Form prepared as a self-assessment, teacher and peer assessment tool to evaluate authentic tasks. The study was conducted with a total of 100 preservice teachers who were third year students at Marmara University, Ataturk Education Faculty's Division of Early Childhood Education during the 20 102011 academic year. Of these 100 preservice teachers, 35 were in the experimental group, 35 in the control-1 group, and 30 in the control-2 group. The results of the study an increase occurred in the academic achievement of all groups from the start to the end of the experiment (p<.01). However, there was a bigger increase in the achievement of the experimental group, where authentic tasks were assigned when compared to the other two (p<.01).
Keywords: authentic learning; authentic task; authentic assessment; peer assessment; self assessment